The Eocene–Oligocene transition: Changes in sea level, temperature or both? - A. J. P. Houben; C. A. van Mourik; A. Montanari; H. Brinkhuis; COCCIONI, RODOLFO (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
The Eocene–Oligocene Transition (EOT ~34 Ma) reflects the onset of major Antarctic glaciation. The primary geochemical signature of the EOT is two ~300 kyr spaced shifts in increasing deep-sea oxygen isotope values, possibly reflecting both global cooling and/or increasing ice volume.Away to assess the respective contribution of continental ice is to quantify concomitant glacio-eustatic sea level change. This is usually expressed in relatively shallow marine depositional settings. One potentially suitable region is in the Vicentinian Alps, NE Italy, where marginal marine deposits document sea level changes during the EOT. By correlating stable isotope-, bio- and magnetostratigraphic information between three distant regions, we are able to relate the shallow marine sections to the Pacific oxygen isotope record fromOcean Drilling Program (ODP) Site 1218 of Coxall et al. (2005). Microfacies, sedimentological, and biotic analysis suggests that associatedwith the first isotope shift (EOT-1) sea level fell ~20 m, and with the ultimate shift, the Oligocene Isotope Event 1 (Oi-1) sea level fell some 50–60 m. Distribution patterns of temperature sensitive dinoflagellates froma coeval central Italian section reveal that the early stages of the EOT were accompanied by sea surface cooling, whereas no sustained cooling is noted in association with the Oi-1. This suggests that the initial EOT shift(s) reflect a mixed signal of ice volume and temperature whereas the Oi-1 primarily reflects expansion of the Antarctic cryosphere.